How Rocket learned to read - Hills, Tad. (New York : Schwartz & Wade Books, 2010)
A little yellow bird teaches Rocket the dog how to read by first introducing him to the "wondrous, mighty, gorgeous alphabet."
Keywords: Reading -- Juvenile fiction; Dogs -- Juvenile fiction; Birds -- Juvenile fiction